Recreational prescription opioid misuse among college students in the USA: An application of the theory of planned behavior - Robert E. Davis; Martha A. Bass; Mary A. Ford; John P. Bentley; KoFan Lee; Nicole A. Doyle (Journal of Health and Social Sciences)
Introduction: Young adults aged 18-25 are at elevated risk for prescription drug misuse compared to other age groups. The purpose of the current study was to utilize the Theory of Planned Behavior (TPB) to predict the intention to engage in recreational prescription opioid misuse (RPOM) among college students while identifying specific salient beliefs that underlie this behavior. Methods: A random sample of college students in the USA completed an electronic survey measuring TPB constructs, salient beliefs, RPOM, and demographic items. Salient beliefs regarding RPOM were identified through a qualitative elicitation process using a subsample (n = 17) of the target population. Content analysis identified specific beliefs that would form questionnaire items to be assessed among the larger sample. Results: Among the entire sample (n = 776), 20.7% reported lifetime RPOM with 11.9% reporting past 6-month RPOM. Ten behavioral, two normative, and eight control beliefs identified in the subsample significantly and positively correlated with intention for RPOM when measured among the entire sample. A staged hierarchical logistic regression model examined the relationship between TPB constructs and intention. With the exception of perceived behavioral control, all constructs were significantly related to intention to engage in RPOM in the next six months. Descriptive norms had the strongest relationship to intention (OR = 1.37, 95% CI 1.23 to 1.54, P < .001), followed by subjective norms (OR = 1.33, 95% CI 1.20 to 1.48, P < .001), and finally attitude (OR = 1.13, 95% CI 1.09 to 1.17, P <.001). Further, attitude significantly moderated the descriptive norm-intention relationship. Conclusion: The beliefs identified by this study may benefit interventions aimed at preventing prescription opioid misuse among this population. Further, targeting global perceptions of peer behavior, as well as, attitudes toward recreational use of prescription opioids may be particularly efficacious.